Modelling Approach on a Gerotor Pump Working in Cavitation Conditions. (November 2016) - Buono, Dario; Cola, Fulvio Domenico Schiano di; Senatore, Adolfo; Frosina, Emma; Buccilli, Giorgio; Harrison, Jonathan
Abstract: Gerotor pumps are widely used on engine hydraulic circuits. The design of these pumps is mainly focused on the study of the leakages through the rotors. Modelling or experimental techniques can be adopted during the components design and optimization phases. The study presented in this paper shows results of a research study made on a gerotor pump. The study has been approached with modeling and experimental techniques. The pump has been tested on a hydraulic bench of the University of Naples "Federico II". Tests have allowed the complete characterization of the pump including in worst conditions like cavitation. In fact, calibrated orifices have been installed on the suction and delivery side of the pump forcing the cavitation. This research is focused on the detection of the cavitation that, as well known, is induced by the low pressure at pump suction, by the presence of air in the pumped oil, by the sloshing of the oil inside the sump and by the recent reduction of sump capability (to reduce maintenance costs). The experimentation phase has been followed by modeling; an accurate model of the pump has been built using the commercial 1D software GT-SUITE. The code developers have added new applications to replicate, with the best accuracy, the experimental data especially in cavitating conditions. The model results have been compared with the experimental data showing a good agreement. The model is able to correctly predict the pump performance including delivery flow rate, total power loss, volumetric efficiency and temperature influence.